2020
DOI: 10.1039/d0qi00780c
|View full text |Cite
|
Sign up to set email alerts
|

A water-stable terbium metal–organic framework as a highly sensitive fluorescent sensor for nitrite

Abstract: With solvothermal method, a novel water-stable Tb-based metal-organic framework (Tb-MOF), namely {[Tb(CA)(OA)0.5(H2O)2]·H2O}n (H2CA = chelidonic acid; H2OA = oxalic acid), was synthesized. Tb-MOF was studied for highly sensitive detection of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 65 publications
0
50
0
Order By: Relevance
“…Two CoO 4 N 2 polyhedrons are connected by two -OCO-groups to generate a dinuclear Co 2 (CO 2 ) 2 SBU with a Co•••Co separation of 4.0417(4) Å. From a topological perspective, the structure can be simplified to a 6-connecting uninodal rob net (point symbol {4 8 •6 6 •8}).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two CoO 4 N 2 polyhedrons are connected by two -OCO-groups to generate a dinuclear Co 2 (CO 2 ) 2 SBU with a Co•••Co separation of 4.0417(4) Å. From a topological perspective, the structure can be simplified to a 6-connecting uninodal rob net (point symbol {4 8 •6 6 •8}).…”
Section: Resultsmentioning
confidence: 99%
“…The development of coordination polymers (CPs) has attracted more and more attention for its application in gas adsorption and separation, photo-or electro-catalysis, fluorescent probes, proton conduction, drug delivery, etc. [1][2][3][4][5][6][7]. However, the first problem to be solved in this field is the rational design structures, which is influenced by many factors (organic ligands, metal ions, solvent system, pH value and reaction temperature, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the boric acid exhibits a strong affinity to fluoride ions, while its interaction with other anions is relatively weak, making it perfect for fluoride selective sensing. Reports on enhancing antenna effect resulted in "turn-on" sensing are rather few comparing to the "turn-off" mechanism discussed above (Karmakar et al, 2019;Fueyo-González et al, 2020;Min et al, 2020;Wang et al, 2020;Yue et al, 2020). However, it is obvious that "turn-on" sensors have advantages over the "turn-off" sensors, especially in the quantitative determination of an analyte in low concentration (Luo et al, 2020).…”
Section: Ratiometric Fluorescent Sensing Mechanismsmentioning
confidence: 99%
“…Reports on enhancing antenna effect resulted in “turn-on” sensing are rather few comparing to the “turn-off” mechanism discussed above ( Karmakar et al, 2019 ; Fueyo-González et al, 2020 ; Min et al, 2020 ; Wang et al, 2020 ; Yue et al, 2020 ). However, it is obvious that “turn-on” sensors have advantages over the “turn-off” sensors, especially in the quantitative determination of an analyte in low concentration ( Luo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sesamol (3,4-methylenedioxyphenol) is a nature antioxidant and exhibited potential neuroprotective effects [ 60 ]. Wang et al [ 61 ] reported a 3D alkaline NMOF (Tb@Sr-MOF) for selectively sensing sesamol.…”
Section: Nmofs For Food Qualitymentioning
confidence: 99%